International trade of Turkish contemporary artworks: an empirical study on the role of artist histoy, institutions and economic and socio-cultural factors in demand - Büyükarslan, Didem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
The exchange of artworks by intermediation of market players yielded economic gains and resulted in an established market. Today, trade of artworks is a dynamic dimension of the global economy. Contemporary art has an important share in the market and witnessed rapid price escalations. In the last decade, Turkey emerged as a new and important player in the global contemporary art market. Previous research streams explored the structure and dynamics of the market, and the role of institutions, the economy and the socio-cultural factors and artist history in demand. Most of the studies however are conceptual. There has been a scarcity of empirical studies on the art market. This study explores the roles of artist history and the environment in the international demand for Turkish contemporary artworks. Data on artists' perceptions and history was collected by a survey conducted on 91 Turkish contemporary artists who participated in the Contemporary Istanbul international art fair. For the statistical analysis of data, frequency, multiple discriminant and multiple regression analyses were employed. The fmdings indicate that perceptions of Turkish contemporary artists on the roles of artist history and the environment, as well as gallery representations and the number of sponsorships of the artists are instrumental in discriminating between artists who do and do not have international sales. Additionally, provenance and gallery representation are strongly related to the number of international sales of artworks by the Turkish contemporary artists.
Keywords: Arts, Turkish -- Marketing.